THE TEST FOR THE APPLICATION OF INTERIM MEASURES IN THE CASE LAW OF THE COURT OF APPEAL OF LITHUANIA - Armalis, Klaidas (Teisė, 2016)
This article contains the analysis of the test for the application of interim measures in the case law of the Court of Appeal of Lithuania, its tendencies and problematic aspects. The article consists of two main parts. The first part is dedicated to the requirement of the likelihood that the plaintiff’s claim could be satisfied. Before 2011, this requirement was not stated expressis verbis in Article 144(1) of the Code of Civil Procedure of Lithuania; however it was, to some extent, being applied in the case law of the Court of Appeal of Lithuania. Such situation led to the eventual amendment of Article 144(1) in 2011. The organic development of the case law in the context of this requirement also led to the situation where the term prima facie, which was being used before the amendment of Article 144(1) and is still in use today, did not develop a consistent and unified meaning. To this day it is used to describe different standards of proof. The second part of the article is dedicated to the analysis of the relationship between the claim amount and the requirement that the execution of the court settlement would become more difficult or impossible without the application of interim measures. The case law of the Court of Appeal of Lithuania contains two different and opposite interpretations of this relationship. In some cases, significant claim amount is considered to imply a presumption of the compliance with this requirement. In other cases, no such conclusion is drawn. The linguistic, systemic analysis of the Code of Civil Procedure and the legal doctrine justifies the critical view of this relationship and forms the basis to further develop the latter case law, where no such relationship is found. The article concludes that the case law of the Court of Appeal of Lithuania regarding the test for the application of interim measures is in continuous development, and collisions between different tendencies are encountered. This, in turn, leads to legal uncertainty. The article also makes a proposal to provide a more concrete definition of the term prima facie in the court rulings regarding interim measures, as well as to link the requirement of the difficult or impossible execution of the court settlement without the application of interim measures with concrete evidence of possible bad faith of the respondent, and not only with the significance of the claim amount.